Combined use of peripheral blood blast count and platelet count during and after induction therapy to predict prognosis in children with acute lymphoblastic leukemia - Dai, Qingkai (Medicine (Baltimore), 2021)
Several studies have reported an association between the rapidity of reduction in peripheral blood blast count or recovery of normal hematopoiesis and treatment outcome during therapy in children with acute lymphoblastic leukemia (ALL). However, little is known about the impact of both of these aspects on prognosis in pediatric ALL. Accordingly, the purpose of this study was to evaluate whether the combined use of blood blast count and platelet count could predict event-free survival (EFS) and overall survival (OS) when minimal residual disease (MRD) detection was not available. A total of 419 patients aged 0 to 14 years diagnosed and treated for ALL between 2011 and 2015 were enrolled. Patients with a blast count ≥0.1 × 10(9)/L on day 8 exhibited significantly lower survival rates than that in those with blast counts <0.1 × 10(9)/L. The EFS and OS in patients with platelet count ≥100 × 10(9)/L on day 33 were significantly higher than those with platelet counts <100 × 10(9)/L. In univariate and multivariate analyses, patients with low blast count on day 8 and high platelet count on day 33 were significantly associated with better EFS and OS. The combination of blast cell count on day 8 and platelet count on day 33 demonstrated a strong association with MRD-based risk stratification. Complete blood count is an inexpensive, easy to perform, and reliable measurement in children with ALL. The combination of blast count and platelet count during and after induction chemotherapy was a significant and independent prognostic factor for treatment outcome in pediatric ALL.